استخدام "الكتاب الذكي" في تعزيز إتقان المفردات اللغة العربية بين طلاب الصف الأول لمنطقة كلانج بولاية سيلانجور : The Use Of “Al-Kitab Az-Zakiy” In Enhancing Vocabulary Mastery Of Arabic Language Among Form 1 Students At Klang, Selangor - Mohd, Nurul Fatihah (SIBAWAYH Arabic Language and Education, 2024)
تم إدراج اللغة العربية كلغة أجنبية في جميع مستويات التعليم في ماليزيا، بدءًا من المرحلة الابتدائية وصولاً إلى الجامعة. تركز عملية اكتساب اللغة على أربع مهارات أساسية: الاستماع، والتحدث، والقراءة، والكتابة. ويعتبر إتقان المفردات أساسًا رئيسيًا لاكتساب هذه المهارات، حيث يمثل حجر الزاوية في تعلم اللغة بشكل فعال. تهدف هذه الدراسة إلى معالجة مشكلة عدم إتقان مفردات اللغة العربية بين طلاب الصف الأول الثانوي ضمن Kurikulum Standard Sekolah Menengah (KSSM) في إحدى المدارس الثانوية في منطقة كلانج، سيلانجور. شارك في هذه الدراسة عينة مكونة من 30 طالبًا من طلاب الصف الأول الثانوي، وتم توظيف أدوات البحث مثل الملاحظة، والأدوات البحثية، والاختبارات القبلية ،والبعدية. استخدمت الدراسة نموذج ADDIE كإطار لمنهجية البحث، مع التركيز على تعزيز المفردات المتعلقة بالفصل الثاني بعنوان "ما أجمل المدرسة". أشارت النتائج الأولية إلى أن الطلاب واجهوا صعوبة في فهم المفردات واستيعابها، مما استدعى استراتيجيات تعزيز أكثر جاذبية وذاكرة. لمواجهة هذه التحديات، تم تصميم وحدة رقمية لتحسين فهم الطلاب وسهولة الوصول إليها. أظهرت نتائج الدراسة أن 56.3٪ من الطلاب في الفصول الدينية قد أحرزوا تقدمًا ملحوظًا في إتقان المفردات. وتؤكد النتائج على أهمية دمج الوسائل التعليمية التكنولوجية جنبًا إلى جنب مع التعليم النظري لتحسين اكتساب المفردات بشكل فعال. Arabic has been integrated as a foreign language across all educational levels in Malaysia, from elementary to university. The language acquisition process focuses on four core skills: listening, speaking, reading, and writing. Central to mastering these skills is a strong foundation in vocabulary, which remains the cornerstone of effective language learning. This study addresses the challenge of insufficient Arabic vocabulary acquisition among Form 1 students under the Kurikulum Standard Sekolah Menengah (KSSM) at secondary school in Klang district, Selangor. A sample of 30 Form 1 students participated in the research, employing observation, research instruments, and pre- and post-tests. The study utilized the ADDIE model as a framework for its research methodology, with a focus on enhancing vocabulary related to Chapter 2, titled "How Beautiful the School Is." Preliminary findings indicated that students faced challenges in comprehending and retaining the vocabulary, necessitating more engaging and memorable reinforcement strategies. To address these challenges, a digital module was designed to improve students’ accessibility and understanding. The study’s results revealed that 56.3% of students in religious classes achieved significant vocabulary mastery. The findings underscore the importance of integrating technological teaching aids alongside theoretical instruction to effectively enhance students’ vocabulary acquisition. Keywords: vocabulary mastery, digital learning, technology integration, teaching aids, Arabic language education